AAGBS Annual Report 2021: at a glance (Master of Islamic Banking and Finance) - UiTM, AAGBS (Arshad Ayub Graduate Business School (AAGBS), 2021)
This program is also recognized by IBFIM where upon completion of the program, students may be awarded a professional certification, Associate Qualification in Islamic Finance (AQIF).